In Vivo Analyses of Osteogenic Activity and Bone Regeneration Capacity of Demineralized Freeze-Dried Bovine Bone Xenograft: A Potential Candidate for Alveolar Bone Fillers - David Buntoro Kamadjaja; Zefry Zainal Abidin; Riska Diana; Ikhram Kharis; Ni Putu Mira Sumarta; Muhammad Subhan Amir; Andra Rizqiawan; Coen Pramono Danudiningrat; Norifumi Nakamura (Hindawi Limited, 2021)
Background. Deproteinized bovine bone mineral (DBBM) particle is the commonly used bone graft substitute in implant surgery which is mainly osteoconductive and has very slow degradation. Demineralized freeze-dried bovine bone xenograft (DFDBBX) particle is being developed as a novel xenogeneic bone filler. Objectives. The study aimed to analyze osteogenic activity and bone-forming capacity of DFDBBX particles compared to DBBM particles in alveolar bone defects in rabbit mandibles models. Material and Methods. This study investigated bone defects whether filled with DBBM particles or DFDBBX particles or left unfilled in 30 rabbit mandibles. Specimens were processed for histology, immunohistochemistry, and micro-CT scanning. Statistical difference was set at a p value < 0.05. Results. The quantitative assessment showed a significantly lower number of osteoclasts and a higher number of osteoblasts in the DFDBBX group compared to the DBBM group in 2 and 4 weeks (p<0.05). Immunostaining analyses showed significantly higher expression of RUNX2, collagen type I, alkaline phosphatase, and osteocalcin in the DFDBBX group compared to the DBBM group in 2 and 4 weeks. Bone healing score in the DFDBBX group was comparable to the DBBM group. Micro-CT presented no significant difference in the volume percentage of the mineralized tissue in the DBBM and DFDBBX groups in spite of the different healing patterns in both groups. Conclusion. DFDBBX particles induced higher osteoblastic activities than DBBM particles at the early stage of healing. Meanwhile, the capacity of bone formation in DFDBBX particles was comparable with DBBM particles at the later stage of healing. Considering the limitation of this study, the results presented DFDBBX particles as potential bone filler candidates.